2021
DOI: 10.46328/ijonses.246
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Visual Arts Teachers’ Attitudes towards Distance Education in the Time of COVID-19

Abstract: In the fight against the 2019 coronavirus disease (COVID-19) pandemic, countries have replaced traditional face-to-face education with distance education as a defense tool. Distance education is not only education and training but also is related to individuals. In today's world, where we are faced with a new development, the conveniences provided by distance education technologies have been used in all areas of education. Therefore, technological developments cause changes in all areas of education systems. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
(46 reference statements)
0
8
1
Order By: Relevance
“…However, studies in the literature also find a negative relationship between age and distance education attitude (17,18). For this reason, although a significant relationship was observed in this study, it needs to be confirmed by more studies on the subject.…”
Section: As Shown Incontrasting
confidence: 53%
“…However, studies in the literature also find a negative relationship between age and distance education attitude (17,18). For this reason, although a significant relationship was observed in this study, it needs to be confirmed by more studies on the subject.…”
Section: As Shown Incontrasting
confidence: 53%
“…However, it turned out that these challenges exacerbated with the COVID-19 aftermath (Cavus et al, 2021;Hartono & Ozturk, 2022;Hu et al, 2021;Jackowicz & Ozturk, 2021;Noroozi & Sahin, 2022;Paudyal & Rana, 2021). More significant challenges, in the whole learning/teaching process, were experienced by teachers, students and parents during the COVID-19 outbreak circumstances (Kara, 2021;Kibici, 2021;Kilincer, 2021;Maksum & Purwanto, 2022;Mishra et al, 2020;Raza et al, 2021). The assessment process was deeply impacted.…”
Section: Introductionmentioning
confidence: 99%
“…Also, creative work develops and exists in the broader context of its sociocultural environment and especially its recipients (Glãveanu, 2014b). Art education enables the child to perceive and evaluate his environment better (Kaleli, 2020a(Kaleli, , 2020b(Kaleli, , 2021Kara, 2021;Kibici & Sarıkaya, 2021;Turhal, 2022;Yağışan & Sünbül, 2009). Art education provides the first step for creativity by teaching not only to look but also to see, hear and hear (Kara, 2022;Kibici, 2021;Ersoy, 1993).…”
Section: Introductionmentioning
confidence: 99%